Ռազմական եզրոյթ-կաղապարների զարգացումը Ղազար Փարպեցու «Պատմութիւն Հայոց» երկում - Կարապետեան, Սիրարփի (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Данное исследование посвящено развитию сложных и словообразовательных моделей слов военного содержания в армянском языке на основе текста «Истории Армении» Газара Парпеци. Важнейшей особенностью современного армянского терминообразования является терминосистема грабара. Военные термины многозначны. Рассматривая данные примеру, мы пришли к выводу, что они не только многозначны, но и представляют преимущественно военную лексику. Ссылаясь на этимологию некоторых корней слов, мы приводим примеры из текста оригинала. Это дает право отметить, что разделение военных терминов и их оценка с современной точки зрения остались неизменными и зафиксированы в современных армянских словарях как исторические словосочетания. Другая же часть, претерпев определенные смысловые изменения, перешла в процессе развития армянского языка на последующие этапы. This study is dedicated to the development of compound and word-formative patterns of words of military content in the Armenian language with respect to Ghazar Parpetsi’s “History of Armenia”. One of the most significant features of the Modern Armenian term-formation is the terminological system of the Classical Armenian Language. Military terms are polysemantic. In examining these words, we concluded that they are not only polysemous, but also have predominantly military meanings. Referring to the etymology of some of the roots of the words, we give examples from the original text. This gives us the right to note that the classifications of military terms and their assessment from a contemporary point of view remained unchanged and are recorded in Modern Armenian dictionaries as historical wordcombinations. The other part, having undergone certain semantic changes, passed to the subsequent stages in the process of development of the Armenian language.
Keywords: Հաղորդումներ